Blurred boundaries and legal uncertainty in police–volunteer partnerships - Hansen Löfstrand, Cecilia (Policing and society, 2020)
Citizen involvement in policing is a means to enhance public confidence in the police and their legitimacy, and to increase their effectiveness. However, governmental control over voluntary policing is fraught with difficulty. We study the relationship between police and citizen volunteers in partnerships, looking specifically at roles and responsibilities in policing and the parties’ reflections upon regulation and autonomy in relation to accountability and legal certainty. Our objective is to illuminate how mutual dependencies in police-volunteer partnerships are managed in practice, and the implications thereof. Two types of police-citizen partnerships in Sweden - the Volunteers of the Police and Missing People Sweden - are explored based on interviews with volunteers and Swedish Police Authority representatives. We show that in police-volunteer partnerships characterised by a high degree of integration of tasks and responsibilities as well as a high degree of trust, boundaries become fuzzy and porous. Despite intentions and great efforts to demarcate what volunteers should and should not do, responsibilities of the state police have been delegated to the extent that civilian participation has gone well into the heart of front-line policing. We discuss the consequences of these blurred boundaries in terms of lack of accountability and legal uncertainty.